Contribution of Smallholder Tree Growers to Increasing Tree Cover in Kaliro District - Kisegu, Derick; Kagaha, David; Whitney, Cory; Tabuti, John R. S. (Springer, Cham., 2019)
Many stakeholders including the Ugandan government are growing trees and contributing to increasing tree cover in Uganda. Whereas the contribution of large-scale tree growers to increasing tree cover has been documented, that of smallholder tree growers (STGs) is not known. But because STGs make up the majority of tree growers, it is possible that their contribution to tree cover in the country is significant. In this study we have addressed this gap for Kaliro District. We have also explored the factors that influence tree planting by STGs. Data was collected in the months of January–June 2017 using interviews with 206 tree growers. Included in the survey were all smallholder farms with 20 or more trees. The tree growers planted 39 species, in the period 1997–2016, the most popular of which were Pinus spp., Eucalyptus spp., Grevillea robusta and Maesopsis eminii. Few STGs planted trees in that time (n = 206) and those who did tended to plant few trees (median 175 trees). Despite the average low contribution by STGs, tree cover is increasing due to a few STGs who planted very many trees. Growers who planted the most trees were male or engaged in small-scale business, possessed a university degree and received support from the government. New approaches may be necessary that provide better access to a greater diversity of smallholder farmers such as women and those without low income and education access. STGs affiliated to tree-growing associations appear to have planted fewer trees than those outside tree-growing associations. Tree growers associations should be redesigned to provide maximum benefit to STGs and local ecology. Income generation was cited as the STGs planters’ main motivation for planting trees. However, the key immediate benefit was firewood. These may be important points to consider when developing interventions that target tree planting in the region and throughout Uganda. We conclude that the contribution of STGs to tree growing in Kaliro District is low and that tree planting campaigns should be inclusive and focus on STGs perceived benefits in order to achieve successful reforestation.
Keywords: Reforestation; Smallholder tree growers; Afforestation; Tree planting; Incentives